Solid-phase extraction of neonicotinoids residue from water : comparison between extraction cartridges - Vuković, Gorica (Array, 2019)
The Commission Implementing Decision (EU) 2018/840 established the watch list of substances for Union-wide monitoring in the field of water policy pursuant to Directive 2008/105/EC and Commission Implementing Decision (EU) 2015/495. This Decision establishes additional substances and their maximum acceptable method detection limits including neonicotinoids (9-500 ng/L). During the pesticides extraction from water, the solid-phase extraction (SPE) column was used. Bakerbond spe™ SDB-1 SPE and Bond Elut Plexa were evaluated for the SPE of neonicotinoids (imidacloprid, thiamethoxam, acetamiprid, thiacloprid and clothianidin) from water. The comparation of the results of these two types of columns, was performed by spiking water samples at two levels (0.05 and 0.1 μg/L) in three replicates. The Bakerbond™ column quantitatively adsorbed these pesticides, with the obtained recoveries: 36.9 % for imidacloprid, 43.2 % for thiacloprid, 119.3 % for clothianidin, 64.6 % for acetamiprid and 53.6 % for thiamethoxam. Using Bond Elut Plexa the obtained recoveries were 66.9 % for imidacloprid, 72.9% for thiacloprid, 103.4 % for clothianidin, 67.4 % for acetamiprid and 45.2% for thiamethoxam. Both colums have low recovery values for thiametoxam, while the highest values were obtained by Bond Elut Plexa for thiacloprid, imidacloprid and acetamiprid. Great recoveries were achieved for clothianidin using both SPE columns.